Memahami Nutrition Facts: Satu Langkah Kecil untuk Hidup Lebih Sehat: Understanding of Nutrition Facts: One Small Step for Healthier Life - Hasanah, Nur; Kurniawati, Yunita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Parents have a central role in determining what their family members will consume, therefore, one of the skills that parents must have is the ability to understand nutrition facts on food packaging. This Community Service aims to provide education to parents of students to improve health literacy in understanding nutrition facts listed on a food or beverage product. The method used is giving a lecture on the material on how to read nutrition facts or nutritional value information, where 56 parents of elementary school students (M = 34.179, SD = 1.086) were involved as audiences. Measurements were taken twice before and after the provision of material to see the effectiveness of the method. The results of the analysis showed that there was a significant difference between the scores before and after the provision of material, which means that education on nutrition facts can improve the health literacy of parents of students regarding nutritional label information on packaged foods.